2005
DOI: 10.1185/030079905x56565
|View full text |Cite
|
Sign up to set email alerts
|

Rivastigmine and donepezil treatment in moderate to moderately-severe Alzheimer's disease over a 2-year period

Abstract: Cholinesterase inhibitor treatment may offer continued therapeutic benefit for up to 2 years in patients with moderate AD. Although both drugs performed similarly on cognition and behaviour, rivastigmine may provide greater benefit in activities of daily living and global functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
0
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(124 citation statements)
references
References 27 publications
2
116
0
6
Order By: Relevance
“…The results have not been consistent (Lehmann et al, 2001), although several have found that the low activity alleles seem to be associated with lower susceptibility to AD and/or later age of onset (Alvarez-Arcaya et al, 2000;Lane et al, 2006Lane et al, , 2008Mateo et al, 2008), or a significantly reduced rate of progression of cognitive decline in individuals with severe AD (Holmes et al, 2005). The presence of the K variant has also been associated with lower benefits from rivastigmine treatment (Bullock et al, 2005). Thus, some studies do suggest a role for BuChE in a disease process (Alzheimer's disease), especially in association with other genetic risk factors such as ApoE4 (Lane et al, 2008), although, as noted earlier, the putative direction of the effect is that the presence of BuChE activity is detrimental rather than protective, and some authors have called for studies to identify cholinesterase inhibitors that are selective for BuChE as potentially advantageous in treatment of AD (Lane et al, 2006).…”
Section: Vic Is Inhibition Of Buche Appropriately Consideredmentioning
confidence: 98%
“…The results have not been consistent (Lehmann et al, 2001), although several have found that the low activity alleles seem to be associated with lower susceptibility to AD and/or later age of onset (Alvarez-Arcaya et al, 2000;Lane et al, 2006Lane et al, , 2008Mateo et al, 2008), or a significantly reduced rate of progression of cognitive decline in individuals with severe AD (Holmes et al, 2005). The presence of the K variant has also been associated with lower benefits from rivastigmine treatment (Bullock et al, 2005). Thus, some studies do suggest a role for BuChE in a disease process (Alzheimer's disease), especially in association with other genetic risk factors such as ApoE4 (Lane et al, 2008), although, as noted earlier, the putative direction of the effect is that the presence of BuChE activity is detrimental rather than protective, and some authors have called for studies to identify cholinesterase inhibitors that are selective for BuChE as potentially advantageous in treatment of AD (Lane et al, 2006).…”
Section: Vic Is Inhibition Of Buche Appropriately Consideredmentioning
confidence: 98%
“…Three randomized controlled trials of cholinesterase inhibitors involving patients with moderate to severe Alzheimer disease [49][50][51] and 2 randomized controlled trials involving only patients with severe Alzheimer disease 52,53 suggested that this class of medication improves cognition, function, behaviour and global measures. The consensus conference recommends their use in patients with severe Alzheimer disease.…”
Section: Management Of Cognitive Declinementioning
confidence: 99%
“…Studies have presented four head-to-head comparisons of ChEI, with donepezil being compared with both rivastigmine [56,57] and galantamine [58,59]. Th ese random ized open-label, rater-blinded trials show similar bene fi ts, but they are methodologically limited.…”
Section: Rationalementioning
confidence: 99%